A compound containing naphthofuran and anthracene and an organic light-emitting device using the compound
By designing a compound containing 呋 有 通过 通过 as the blue light main material of organic luminous devices, the existing materials are resolved in terms of stability and luminous performance, and organic lighting devices with high efficiency and long life.
Patent Information
- Application Number
- CN202310222392.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-09
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-03-09
AI Technical Summary
The blue light host material of existing organic electroluminescent materials has shortcomings in terms of stability and luminescence performance, which limits the industrialization of organic light emitting devices.
Design a compound containing 呋 种 设计, and its structured formula (i) ~ (III), which is used as a luminous layer Blu -ray main material for organic lighting devices.
This compound has good thermal stability and excellent luminous performance, and can effectively improve the lighting efficiency and service life of organic light -emitting devices.
Smart Images

Figure QLYQS_1 
Figure BDA0004117229840000021 
Figure BDA0004117229840000031
Abstract
Description
Technical Field
[0001] The present invention relates to a compound containing naphthofuran and anthracene that can be used in an organic light-emitting element and an organic light-emitting device using the compound, and in particular to a compound containing naphthofuran and anthracene that can be used in a light-emitting layer in an organic light-emitting element to achieve element characteristics such as high luminous efficiency, long life and low voltage driving, an organic light-emitting device using the compound, and an organic light-emitting element including the compound. Background Art
[0002] Organic light emitting diodes (OLEDs) are display components that utilize the phenomenon of self-luminescence and have a wide viewing angle. Compared with liquid crystal display components, OLED components are thinner and lighter, have a faster response speed, and can achieve flexible displays. Therefore, their application as full-color display components or lighting equipment is highly anticipated.
[0003] Generally, organic light emitting phenomenon refers to the phenomenon of converting electrical energy into light energy using organic substances. An organic light emitting element using the organic light emitting phenomenon generally has a structure including an anode, a cathode, and an organic material layer interposed between the anode and the cathode.
[0004] Among them, the organic layer is composed of a multilayer structure composed of different substances in most cases in order to improve the efficiency and stability of the organic light-emitting element. For example, it can be composed of a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, etc. If a voltage is applied between the two electrodes in the structure of such an organic light-emitting element, the holes in the anode will be injected into the organic layer, and the electrons in the cathode will also be injected into the organic layer. When the injected holes and electrons meet in the light-emitting layer, excitons are formed. When the excitons release energy and transition to the ground state, photons will be emitted, thereby generating light. Such organic light-emitting elements are widely recognized to have the characteristics of self-luminescence, high brightness, high efficiency, low driving voltage, wide viewing angle, high contrast, and high-speed responsiveness.
[0005] At present, the research on organic electroluminescent materials has been widely carried out in academia and industry. Among them, blue light host materials are an important component of organic electroluminescent devices. There is still a lot of room for improvement in the stability and luminescence performance of blue light host materials, which restricts the industrialization of light-emitting devices. Therefore, designing and finding a compound as a new OLED material to overcome its shortcomings in practical applications is the focus of OLED material research and the future research and development trend. Summary of the invention
[0006] The object of the present invention is to provide a compound containing naphthofuran and anthracene and an organic light-emitting device using the compound. The compound has good thermal stability, and the light-emitting device prepared by using the compound has high luminous efficiency and service life.
[0007] The present invention provides a compound containing naphthofuran and anthracene, the general structural formula of which is shown in formula (I) or (II) or (III)
[0008]
[0009] Wherein, R1 and R2 are independently selected from substituted or unsubstituted C6 to C 30 Aromatic hydrocarbon or C6~C 30 An aromatic heterocyclic group.
[0010] Preferably, the aromatic hydrocarbon group is selected from phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, indenyl, fluorenyl, perylenyl, phenanthrenyl, pyrenyl, fluoranthenyl or triphenylenyl.
[0011] Preferably, the heteroatom in the aromatic heterocyclic group is oxygen or sulfur.
[0012] Preferably, the aromatic heterocyclic group is selected from benzofuran, benzothiophene, dibenzofuran or dibenzothiophene, benzofuranthiophene, etc., more preferably dibenzofuran or dibenzothiophene.
[0013] Preferably, the compound containing naphthofuran and anthracene is as shown in any one of Formulas 1 to 90, and the hydrogen atoms in the following Formulas 1 to 90 may be replaced by deuterium atoms, which is also within the protection scope of the present invention:
[0014]
[0015]
[0016]
[0017] The present invention also provides an organic light-emitting device, which comprises the compound containing naphthofuran and anthracene.
[0018] Preferably, the organic light-emitting device comprises a first electrode, a second electrode and an organic layer disposed between the first electrode and the second electrode; the organic layer comprises the compound containing naphthofuran and anthracene.
[0019] Preferably, the organic layer is a light-emitting layer, and the compound containing naphthofuran and anthracene is used as a blue light host material of the light-emitting layer.
[0020] Beneficial effects of the present invention:
[0021] Compared with the prior art, the present invention provides a compound containing naphthofuran and anthracene and an organic light-emitting device using the compound. The compound containing naphthofuran and anthracene has a structure shown in formula (I) to (III). The compound containing naphthofuran and anthracene of the present invention has good thermal stability and excellent luminescence performance, and can be used to prepare organic electroluminescent devices, especially as a blue light host material in organic electroluminescent devices, and can effectively improve the luminescence efficiency and service life of organic light-emitting devices. DETAILED DESCRIPTION
[0022] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0023] It should be noted that, unless otherwise specified, the meanings of the scientific and technical terms used in the present invention are the same as those generally understood by those skilled in the art.
[0024] The aromatic hydrocarbon group described in the present invention refers to a general term for a monovalent group remaining after removing a hydrogen atom from the aromatic carbon nucleus of an aromatic hydrocarbon molecule, which can be a monocyclic aromatic group or a condensed aromatic group, for example, can be selected from phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, indenyl, fluorenyl, perylenyl, phenanthrenyl, pyrenyl, fluoranthenyl or triphenylenyl, but is not limited thereto.
[0025] The aromatic heterocyclic group of the present invention refers to a general term for a group in which one or more aromatic carbon atoms in an aromatic group are replaced by a heteroatom, wherein the heteroatom includes but is not limited to oxygen and sulfur. The heteroaryl group may be a monocyclic heteroaryl group or a condensed-ring heteroaryl group, for example, selected from benzofuran, benzothiophene, dibenzofuran, dibenzothiophene, benzofuran-thiophene, etc., but is not limited thereto.
[0026] The present invention first provides a compound containing naphthofuran and anthracene, the general structural formula of which is shown in formula (I) to (III):
[0027]
[0028] Wherein R1 and R2 are independently selected from substituted or unsubstituted aromatic hydrocarbon groups, or substituted or unsubstituted aromatic heterocyclic groups.
[0029] According to the present invention, R1 and R2 are independently selected from substituted or unsubstituted C6 to C 30 Aromatic hydrocarbon group, or substituted or unsubstituted C6~C 30 More specifically, it is preferably selected from phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, indenyl, fluorenyl, perylenyl, phenanthrenyl, pyrenyl, fluoranthenyl or triphenylenyl. The heteroatom in the aromatic heterocyclic group is oxygen or sulfur, and is preferably selected from dibenzofuran or dibenzothiophene.
[0030] According to the present invention, the compound containing naphthofuran and anthracene is preferably as shown in any one of Formulas 1 to 90, and the hydrogen atoms in the following Formulas 1 to 90 may be replaced by deuterium atoms, which is also within the protection scope of the present invention:
[0031]
[0032]
[0033]
[0034] Some specific structural forms of the compounds containing naphthofuran and anthracene described in the present invention are listed above, but the compounds containing naphthofuran and anthracene described in the present invention are not limited to these listed chemical structures. All compounds based on the structures shown in formulas (I) to (III) and in which R1 and R2 are the groups defined above should be included.
[0035] The method for preparing the compound containing naphthofuran and anthracene of the present invention has a reaction route as shown in the following general formula.
[0036]
[0037] The present invention has no special requirements for the conditions of the above reaction, and the conventional conditions of such reactions well known to those skilled in the art can be used. The present invention has no particular restrictions on the source of the raw materials used in the above reaction, and the raw materials or intermediates can be commercially available products or prepared by preparation methods well known to those skilled in the art. Wherein, the selection of R1 and R2 is as described above, and will not be repeated here.
[0038] For the compound containing naphthofuran and anthracene provided by the present invention, the synthesis method thereof can be other reaction types well known to those skilled in the art, and the above reaction formula is only a feasible one.
[0039] The present invention also provides an organic light-emitting device, comprising the compound containing naphthofuran and anthracene. The organic light-emitting device can be an organic light-emitting device well known to those skilled in the art. The organic light-emitting device of the present invention preferably comprises a first electrode, a second electrode and an organic layer disposed between the first electrode and the second electrode; the organic layer comprises the compound containing naphthofuran and anthracene. The organic layer may include at least one of a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer and an electron injection layer. Preferably, the compound containing naphthofuran and anthracene is used as a blue light host material in the organic layer.
[0040] The present invention has no particular limitation on the sources of the raw materials used in the following examples, and the raw materials may be products directly sold on the market or prepared by methods well known to those skilled in the art.
[0041] Example 1: Synthesis of Intermediate Ia
[0042]
[0043] Add 20 g (0.09 mol) of 3-bromo-2-naphthol, 28.1 g of triethylamine (0.278 mol) and 500 mL of dichloromethane to the reaction flask, add 10.4 g of acetic anhydride (0.102 mol) dropwise at 0 ° C. After the addition is complete, stir at 25 ° C. for 16 h, then add 100 ml of 10% by mass aqueous hydrochloric acid to quench the reaction, separate the liquids, wash the organic phase with water until neutral, dry the organic phase with 100 g of anhydrous magnesium sulfate, and concentrate to obtain 21.3 g of a yellow solid with a purity of 99.5% and a yield of 90%.
[0044] Ia-A2
[0045] 26 g la-A1 (0.1 mol), 300 ml triethylamine and 300 ml DMF were added to the reaction bottle, and 11.8 g trimethylsilylacetylene (0.12 mol), 2.21 g (0.003 mol) Pd(Ph3P)2Cl2, and 1.14 g (0.006 mol) Cul were added. After stirring at 25°C for 16 h, 100 ml of 10% by mass aqueous hydrochloric acid solution was added to quench the reaction, and then 500 ml * 3 of dichloromethane was added to extract the product. The dichloromethane phases were combined, washed four times with 200 ml * 4 of water, dried with 100 g of anhydrous magnesium sulfate, and passed through a chromatography column filled with 100 g silica gel (200-300 mesh). The column liquid was concentrated to obtain 25.4 g of a light yellow solid with a purity of 99.2% and a yield of 90%.
[0046] Ia-A3
[0047] Add 25.4 g (0.09 mol) of Ia-A2, 130 g of cesium carbonate (0.4 mol), 800 ml of DMF, and 100 ml of water to a reaction flask, and react at 80°C for 5 h. Then cool to room temperature, pour the reaction solution into 2 L of saturated aqueous ammonium chloride solution to precipitate the product, and directly filter it. Wash the resulting solid three times with 50 ml*3 of water. Dissolve the resulting solid in 200 ml of dichloromethane and pass it through a chromatography column filled with 50 g of silica gel (200-300 mesh). Concentrate the column liquid to obtain 11.8 g of light yellow crystals Ia-A3 with a purity of 98.5% and a yield of 78%.
[0048] Ia
[0049] Take 3.36g (0.02mol) of la-A3 and dissolve it in 50ml of tetrahydrofuran, cool it down to -80℃ under nitrogen protection, add 10ml of 2.5M butyl lithium (0.025mol) dropwise, keep the system temperature at -80~-75℃ for 2h after the addition is complete, add 3.12g (0.03mol) of trimethyl borate dropwise, slowly warm it to room temperature after the addition is complete, take samples and send them for inspection. After the raw material reaction is complete, add 100ml of 1M dilute hydrochloric acid dropwise, and stir at room temperature for 30min. Separate the liquid, extract the aqueous phase with 50ml*3 ethyl acetate 3 times, combine the organic phases and concentrate to dryness, add 10ml of n-heptane to the obtained viscous material, reduce to 0℃ and keep warm for 1h, and precipitate the product. Filter by suction to obtain 2g of solid, purity 99.4%, yield 50%. The total yield of the four-step reaction is 31.6%.
[0050] Mass spectrum m / z: 212.02 (calculated value: 212.06). Theoretical element content (%) C 12 H9 B O3: C, 67.98; H, 4.28; B, 5.10; O, 22.64. Measured element content (%): C, 67.96; H, 4.30; B, 5.09.
[0051] The following intermediate compounds were obtained in a similar manner:
[0052] Table 1
[0053]
[0054] Example 2: Synthesis of Intermediate 1-A2
[0055]
[0056] Synthesis of intermediate 1-A1
[0057] 21.2 g (0.1 mol) of la and 15.7 g (0.1 mol) of bromobenzene, 20.7 g (0.15 mol) of potassium carbonate, and 0.021 g of Pd-132 (dichlorodi-tert-butyl-(4-dimethylaminophenyl)phosphine palladium (II)) were added to a 1 L reaction bottle, and 200 ml of toluene, 100 ml of ethanol and 100 ml of water were added. The reaction was carried out at 80 ° C for 12 h under nitrogen insulation. The reaction of the raw materials was completed under TLC monitoring. The organic phase was combined and washed twice with 300 ml * 2 of water. After the organic phase was dried, it was passed through a chromatography column filled with 50 g of silica gel (200-300 mesh). The column liquid was concentrated to dryness, 100 ml of ethanol and 20 ml of toluene were added, the temperature was raised to 80 ° C to dissolve, and then 20 ml of water was slowly added dropwise. Then, the temperature was lowered to room temperature and filtered to obtain solid 1-A1, which was dried to obtain 17.8 g. The purity was 99.7% and the yield was 73%.
[0058] Synthesis of Intermediate 1-A2
[0059] 17.8g (0.073mol) 1-A1 and 22.5g (0.1mol) NIS were added to 200ml THF, and the mixture was kept at 60°C for 16 hours under nitrogen protection. After gas phase monitoring, the reaction of the raw materials was completed. 100ml ethanol and 2L water were added to precipitate solids, which were filtered off with suction. The filter cake was refluxed and beaten with 200ml water for 1h, cooled to room temperature and filtered off with suction. Then, 50ml ethanol was refluxed and beaten for 1h, cooled to room temperature and filtered off with suction. The filter cake was sampled and sent for inspection. The main purity was 99.7%. 12.16g was obtained after drying. The yield of this step was 45%, and the total yield was 32.85%.
[0060] Compound 1-A2 mass spectrum m / z: 370.12 (calculated value: 369.99). Theoretical element content (%) C 18 H 11 IO: C, 58.40; H, 3.00; I, 34.28; O, 4.32. Measured element content (%): C, 58.38; H, 3.02; I, 34.27.
[0061] NMR data of compound 1-A2: 1H-NMR (Bruker, Switzerland, AvanccII400MHz NMR spectrometer, CDCl3), δ8.62 (d, 1H), δ8.33 (m, 1H), δ8.12~8.04 (m, 3H), δ7.85 (m, 1H), δ7.70 (m, 1H), δ7.57 (m, 3H), δ7.39 (m, 1H).
[0062] The following intermediate compounds were obtained in a similar manner:
[0063] Table 2
[0064]
[0065]
[0066] Example 3: Synthesis of Compound 1
[0067]
[0068] 24.3 g (0.065 mol) of intermediate 1-A2, 25.5 g (0.085 mol) of 1-B, 17.6 g (0.127 mol) of potassium carbonate, and 0.025 g of Pd-132 (dichlorodi-tert-butyl-(4-dimethylaminophenyl)phosphine palladium (II)) were added to a 1 L reaction bottle, and 300 ml of toluene, 150 ml of ethanol and 150 ml of water were added. The reaction was carried out at 80° C. under nitrogen for 12 h and monitored by TLC. After the reaction of the raw materials is completed, the temperature is cooled to room temperature and filtered. The filter cake is refluxed with 300 ml of water for 1 hour, filtered, and then refluxed with 50 ml of ethanol for 1 hour and cooled to room temperature for filtration. The filter cake is refluxed with 2L of toluene to dissolve it and then passed through a chromatography column filled with 100 g of silica gel (200-300 mesh). The chromatographic liquid is concentrated to about 200 ml, cooled to room temperature and filtered. The filter cake is dried to obtain 22.5 g, with a main purity of 99.92% and a yield of 70%.
[0069] Mass spectrum m / z: 496.20 (calculated value: 496.18). Theoretical element content (%) C 38 H 24 O: C, 91.91; H, 4.87; O, 3.22. Measured element content (%): C, 91.90; H, 4.88. The above results confirm that the obtained product is the target product.
[0070] Example 4: Synthesis of Compound 49
[0071]
[0072] Synthesis of Intermediate 49-A1
[0073] 21.2 g (0.1 mol) of II-a and 25.7 g (0.1 mol) of 9-bromophenanthrene, 20.7 g (0.15 mol) of potassium carbonate, and 0.021 g of Pd-132 (dichlorodi-tert-butyl-(4-dimethylaminophenyl)phosphine palladium (II)) were added to a 1 L reaction bottle, and 200 ml of toluene, 100 ml of ethanol and 100 ml of water were added, and the reaction was carried out at 80°C under nitrogen for 12 h and monitored by TLC. After the reaction of the raw materials is completed, the liquids are separated, washed with water and extracted twice with 100ml*2 toluene, the organic phases are combined, washed twice with 300ml*2 water, and the organic phase is dried and passed through a chromatography column filled with 50g silica gel (200-300 mesh). The column liquid is concentrated to dryness, 100ml ethanol and 20ml toluene are added, the temperature is raised to 80°C to dissolve, and then 20ml water is slowly added dropwise. The temperature is then lowered to room temperature and filtered to obtain solid 49-A1, which is dried to obtain 19.2g with a purity of 99.7% and a yield of 56%.
[0074] Synthesis of Intermediate 49-A2
[0075] 19.2g (0.056mol) 49-A1 and 16.4g (0.073mol) NIS were added to 200ml THF, and the mixture was kept at 60°C for 16 hours under nitrogen protection. The reaction of the raw materials was completed by gas phase monitoring. The solid was precipitated with 100ml ethanol and 2L water, and filtered. The filter cake was refluxed and beaten with 200ml water for 1h, cooled to room temperature and filtered. Then, 50ml ethanol was refluxed and beaten for 1h, cooled to room temperature and filtered. The filter cake was sampled and sent for inspection. The main purity was 99.7%. 11.2g was obtained after drying. The yield of this step was 42.5%.
[0076] Synthesis of compound 49
[0077] 22.4 g (0.0476 mol) of intermediate 49-A2, 24.86 g (0.0714 mol) of 9-(1-naphthyl)-10-anthraceneboric acid, 13.8 g (0.1 mol) of potassium carbonate, and 0.022 g of Pd-132 (dichlorodi-tert-butyl-(4-dimethylaminophenyl)phosphine palladium (II)) were added to a 1 L reaction bottle, and 250 ml of toluene, 100 ml of ethanol and 100 ml of water were added. The reaction was carried out at 80°C under nitrogen for 12 h and monitored by TLC. After the reaction of the raw materials was completed, the mixture was cooled to room temperature and filtered. The filter cake was refluxed with 300 ml of water for 1 hour, filtered, and then refluxed with 50 ml of ethanol for 1 hour and cooled to room temperature for filtration. The filter cake was dissolved in 2L of toluene and passed through a chromatography column filled with 100 g of silica gel (200-300 mesh). The chromatographic liquid was concentrated to about 200 ml, cooled to room temperature and filtered. The filter cake was dried to obtain 20.9 g, with a main purity of 99.89% and a yield of 68%.
[0078] Mass spectrum m / z: 646.22 (calculated value: 646.23). Theoretical element content (%) C 50 H 30 O: C, 92.85; H, 4.68; O, 2.47. Measured element content (%): C, 92.86; H, 4.68. The above results confirm that the obtained product is the target product.
[0079] Example 5: Synthesis of Compound 81
[0080]
[0081] Synthesis of Intermediate 81-A1
[0082] 21.2 g (0.1 mol) of III-a, 15.7 g (0.1 mol) of bromobenzene, 20.7 g (0.15 mol) of potassium carbonate, and 0.021 g of Pd-132 (dichlorodi-tert-butyl-(4-dimethylaminophenyl)phosphine palladium (II)) were added to a 1 L reaction bottle, and 200 ml of toluene, 100 ml of ethanol and 100 ml of water were added, and the reaction was carried out at 80° C. under nitrogen for 12 h and monitored by TLC. After the reaction of the raw materials is completed, the liquids are separated, washed with water and extracted twice with 100ml*2 toluene, the organic phases are combined, washed twice with 300ml*2 water, and the organic phase is dried and passed through a chromatography column filled with 50g silica gel (200-300 mesh). The column liquid is concentrated to dryness, 100ml ethanol and 20ml toluene are added, the temperature is raised to 80°C to dissolve, and then 20ml water is slowly added dropwise. The temperature is then lowered to room temperature and filtered to obtain solid 81-A1, which is dried to obtain 18.5g with a purity of 99.7% and a yield of 76%.
[0083] Synthesis of Intermediate 81-A2
[0084] 18.5 g (0.076 mol) of 81-A1 and 22.5 g (0.1 mol) of NIS were added to 200 ml of THF, and the mixture was kept at 60°C for 16 hours under nitrogen protection. The reaction of the raw materials was completed by gas phase monitoring. The solid was precipitated with 100 ml of ethanol and 2 L of water, and filtered. The filter cake was refluxed and beaten with 200 ml of water for 1 hour, cooled to room temperature and filtered. Then, 50 ml of ethanol was refluxed and beaten for 1 hour, cooled to room temperature and filtered. The filter cake was sampled and sent for inspection. The main purity was 99.1%. 12.4 g was obtained after drying. The yield of this step was 44%.
[0085] Synthesis of compound 81
[0086] 24.3 g (0.067 mol) of intermediate 81-A2, 38.9 g (0.1 mol) of 81-B, 20.7 g (0.15 mol) of potassium carbonate, and 0.024 g of Pd-132 (dichlorodi-tert-butyl-(4-dimethylaminophenyl)phosphine palladium (II)) were added to a 1 L reaction bottle, and 300 ml of toluene, 150 ml of ethanol and 150 ml of water were added. The reaction was carried out at 80°C under nitrogen for 12 h and monitored by TLC. After the reaction of the raw materials is completed, the temperature is cooled to room temperature and filtered. The filter cake is refluxed with 300 ml of water for 1 hour, filtered, and then refluxed with 50 ml of ethanol for 1 hour and cooled to room temperature for filtration. The filter cake is dissolved in 2L of toluene and then passed through a chromatography column filled with 100 g of silica gel (200-300 mesh). The chromatographic liquid is concentrated to about 200 ml, cooled to room temperature and filtered. The filter cake is dried to obtain 25.5 g, with a main purity of 99.86% and a yield of 65%.
[0087] Mass spectrum m / z: 586.21 (calculated value: 586.19). Theoretical element content (%) C44 H 26 O2: C, 90.08; H, 4.47; O, 5.45. Measured element content (%): C, 90.06; H, 4.48. The above results confirm that the obtained product is the target product.
[0088] Other compounds can be obtained by similar synthetic methods.
[0089] In the present invention, the specific structure of the materials used in the following application examples is as follows:
[0090]
[0091] Device Example 1
[0092] The device embodiment provides an organic electroluminescent device, using the compound 1 provided in Synthesis Example 1 of the present invention as the main material of the light-emitting layer; the structure of the organic electroluminescent device is:
[0093] ITO / HT (40nm) / light-emitting layer main material: BD-23% (30nm) / TPBI (30nm) / LiF (0.8nm) / Al (150nm).
[0094] The preparation method of the organic electroluminescent device is as follows:
[0095] The glass substrate coated with an ITO transparent conductive layer (as an anode) was ultrasonically treated in a cleaning agent, then rinsed in deionized water, ultrasonically degreased in a mixed solvent of acetone and ethanol, and then baked in a clean environment until the water was completely removed. It was cleaned with ultraviolet light and ozone, and the surface was bombarded with a low-energy cation beam to improve the surface properties and enhance the bonding ability with the hole layer.
[0096] The materials are placed in a vacuum chamber, evacuated to 1×10-5~1×10-6Pa, and then vacuum-deposited onto the cleaned ITO substrate in sequence. Among them, the main material of the light-emitting layer: BD-23% (30nm) means that in the device, the main material of the light-emitting layer and BD-2 are co-evaporated at a volume ratio of 97:3 to form a light-emitting layer, and the thickness of the light-emitting layer is 30nm.
[0097] Device Examples 2-10
[0098] Device Examples 2-10 respectively provide an organic electroluminescent device, which differs from Device Example 1 only in that the main material of the light-emitting layer is different (see Table 3 below for details), and other conditions are the same as those of Device Example 1.
[0099] Device Examples 11-13
[0100] Device Examples 11-13 respectively provide an organic electroluminescent device, which differs from Device Example 1 only in that the main material of the light-emitting layer is different, and BD-3 is used instead of BD-2 (see Table 3 below for details), and other conditions are the same as Device Example 1.
[0101] Device Comparison Examples 1-7
[0102] Device Comparative Examples 1-7 respectively provide an organic electroluminescent device, which is different from Device Example 1 only in that the main body of the light-emitting layer is different (see Table 3 below for details), and other conditions are the same as those of Device Example 1.
[0103] Performance Testing
[0104] Test method: Use the OLED-1000 multi-channel accelerated aging life and light color performance analysis system produced by Hangzhou Yuanfang to test the driving voltage, current efficiency and life LT90 of the OLED devices provided above; where LT90 refers to the time required for the brightness to drop to 90% of the original brightness while maintaining the current density at the initial brightness of 1000nit. The test items include the brightness, driving voltage, and current efficiency of the organic electroluminescent device. The driving voltage, current efficiency, and LT90 data are all relative values when the brightness is 1000cd / m2. The performance test results of the organic electroluminescent device are shown in Table 3 below:
[0105] Table 3
[0106]
[0107]
[0108] It can be seen from the contents of Table 3 that the present invention obtains compounds having naphthofuran and anthracene through molecular design. The compounds having naphthofuran and anthracene structures provided by the present invention can be used as the main material of the light-emitting layer of an OLED light-emitting device, so that the OLED light-emitting device has a lower driving voltage, a higher current efficiency and a longer life.
[0109] Furthermore, when the compound having naphthofuran and anthracene structures of the present invention is used as the main material of the light-emitting layer of an OLED light-emitting device and is combined with BD-3, the performance is further improved.
[0110] The present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. The following compounds containing naphthofuran and anthracene:
2. An organic light-emitting device, characterized in that: The compound comprising naphthofuran and anthracene as claimed in claim 1.
3. The organic light-emitting device according to claim 2, characterized in that: The invention comprises a first electrode, a second electrode and an organic layer arranged between the first electrode and the second electrode; the organic layer comprises the compound containing naphthofuran and anthracene as claimed in claim 1.
4. The organic light-emitting device according to any one of claims 2 to 3, characterized in that: The organic layer is a light-emitting layer, and the compound containing naphthofuran and anthracene is used as a blue light host material of the light-emitting layer.
Citation Information
Patent Citations
Electroactive compounds
CN114514225A
KR20240003039A